HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN DIET HIPERTENSI PADA PENDERITA HIPERTENSI DI KELURAHAN TAPOS DEPOK - Rosa Amelia; Indah Kurniawati2 (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
The prevalence of hypertension will continue to increase globally and it is predicted that by2025 there will be a high increase of around 1.15 billion cases of hypertension worldwide.Hypertension that does not get good treatment will cause complications and death. Patientwith hypertension need family support is needed for a hypertensive diet. This study aims todetermine the relationship of family support for adherence to the hypertension diet inhypertensive patients in Tapos Depok Village. This research method uses a cross-sectionalresearch design. This research was conducted in Tapos Depok Village with a total sample of93 respondents. Sampling in this study using cluster sampling method and Simple RandomSampling technique. Data analysis using the Chi-Square test. The results obtained valuesp=0.001, which means there is a relationship between family support for compliance withhypertension diet in hypertensive patients in Tapos Depok Village. Obtained values OR=5,704which means respondents who received good family support will more easily comply with theirhypertension diet, compared with respondents who did not family support.